A numerical study on structural behaviour of lean duplex stainless steel tubular beams with rectangular web openings. (August 2021) - Lepcha, Karma Hissey; Patton, M Longshithung
Abstract: This paper investigates the flexural behaviour of Lean Duplex Stainless Steel (LDSS) rectangular tubular beams with rectangular web openings located centrally. The analysis procedures for the FE models were verified by validating with test results conducted by different authors for the perforated open sections as well as unperforated tubular sections. In order to study the effect of perforation on the structural response of Rectangular Hollow Sections (RHS), rectangular perforation is chosen with steel tube thicknesses ranging from 0.8 mm to 3.0 mm. It is observed that there is a linear decrease in moment capacities of the section with increase in the size of openings with local buckling being more predominant in the case of slender sections as compared to the stocky sections. The section capacities obtained were compared with the design strength calculated against the EN1993-1–4 (2006), ASCE8-02, the direct strength method (DSM) and the continuous strength method (CSM). The design strength calculated for perforated beams with respect to the CSM method gave the best predictions for strength calculation.